Good Mosque, bad Mosque: boundaries to belonging in contemporary Germany - Becker-Topkara, Elisabeth (Journal of the American Academy of Religion, 2017)
How do Muslim institutions in Europe relate to national and European values? How do they visibly challenge boundaries that other/exclude Islam? This analysis identifies two factors that result in the acceptance or rejection of mosques, showing the boundary work at play in this process: (1) the ability of Muslim leadership to achieve a positive visibility of the mosque through the performance and staging of key German civic ideals; and (2) the role of local contexts of reception. Through ethnography, interview data, and analysis of newspaper coverage of the Penzberg Mosque and the Cologne Mosque, I argue that the strategic presentation of both form and function by Muslim communities interacts with constraining environmental factors in delineating possibilities of belonging. This leads to the labeling of mosques as “good” or “bad,” evoking the “good Muslim”/“bad Muslim” binary.